EFFECT OF ANKLE JOINT LIMITATION ON WALKING ABILITY IN DIFFERENT NEUROMUSCULAR DISEASES - Kaya, Pinar; Alemdaroglu, Ipek; YILMAZ, ÖZNUR; Karaduman, Ayse; Topaloglu, Haluk (My University, 2014)
Purpose: In this study, we aimed to investigate the impact of the ankle limitation on the walking ability among two groups that have different spatial distribution of the weakness.